Análise de viabilidade econômico-financeira para loteamentos: estudo de caso de uma empresa da cidade de Nova Santa Rita - Hansen, Nicole Barcelos (Universidade do Vale do Rio dos Sinos, 2022)
The subdivision is a modality of Urban Land Development and is inserted in the real estate market, which significantly impacts the generation of income and jobs in the country. This sector has faced several adversities in recent years, such as low sales volume and high inflation. In this scenario, companies are more prone to a reduction of their profits and therefore need a careful evaluation of their real estate projects. Thus, in order to reduce business risks and uncertainties, the objective of this research was to conduct an economic-financial feasibility study for a subdivision located in the city of Nova Santa Rita, based on investment indicators, using the scenario analysis method. In order to meet the objectives of this monograph, a literature review was carried out, and from this literature search, the scope of the economic-financial feasibility study was defined. With this, the premises were established and the interview planning was carried out to gather the parameters from the company. Through the interview, the data base was obtained to compose the necessary premises of this research. Thus, the development of the case study began, in which the information of the subdivision was gathered and the values and specificities of the variables that compose the cash flows were defined, followed by the development of the physical-financial schedules of the stages of the subdivision. Therefore, the five scenarios proposed in this study were prospected and the values and conditions of the variables of each one were established, which were projected throughout their duration periods. Finally, the cash flows of all scenarios were elaborated, which enabled the calculation of the following indicators: Net Present Value (NPV); Profitability Index (IL); Internal Rate of Return (IRR), and Discounted Payback (PBD). The analysis of these results in conjunction with the literature allowed us to identify that the subdivision has potential for success. It was concluded that the study developed contributes to the economic-financial feasibility analysis of the company's new subdivisions, aiming at more assertive decision making for risk reduction.
Keywords: Análise de cenários; Empreendimentos imobiliários; Loteamento; Viabilidade econômico-financeira; Scenario analysis; Real estate ventures; Subdivision; Economic-financial feasibility